Subprime Attention Crisis: Advertising and the Time Bomb at the Heart of the Internet - Holmes, Jim (Journal of Telecommunications and the Digital Economy, 2021)
In 2020, Tim Hwang, a writer, lawyer and technology policy researcher based in New York, published a short book entitled Subprime Attention Crisis: Advertising and the Time Bomb at the Heart of the Internet, which seeks to analyse the issues that are developing around the business model associated with the continued operation of the Internet, at least in its current manifestation, and the weaknesses and potential instability associated with that model. The book is of particular interest because the problems and possible next developments of the “time bomb” are set out in a plausible manner, together with some discussion on possible solutions. In particular, the author makes a credible comparison of the business model of the Internet with the subprime mortgage securities sector, the collapse of which contributed to the Global Financial Crisis in 2008.